THE IMPLEMENTATION OF CONTENT-BASED INSTRUCTION (CBI) FOR THE TEACHING OF PHYSICS AT RSBI CLASS IN SMP N 1 PURWODADI: A MICRO ETHNOGRAPHY - SULISTYOWATI, DEFI (2011)
The objectives of this study are describing the implementation of Content-Based Instruction (CBI) for teaching Physics, especially on objective of learning, the material, classroom activities, strengths and weaknesses of the method used. The result of this study is intended to give evaluation of teaching Physics in RSBI class implemented CBI. This is a micro ethnography research. The object of the study is the implementation of CBI for the teaching Physics of RSBI class. The methods of collecting data are observation, documentation, and interview. In analyzing of data the writer applied descriptive qualitative research consisting of data reduction, data display, and conclusion drawing. The results of this research show that the model of CBI implemented in teaching Physics of RSBI class belongs to immersion model. Then, the syllabus and lesson plan have made in English well. Furthermore, in teaching Physics activities, the teacher still delivers and explains the material to the students 70% in Indonesia and 30% in English. In addition, the teacher has several roles as the classroom manager, facilitator, counselor, motivator and evaluator. Then, the student's role is as the listener and the performer. The strengths of CBI in teaching Physics are the students are rich of concept of Physics in Indonesia and English and the students get the concept more by ICT. Finally, the weaknesses of CBI in teaching Physics are the students get nervous to express their idea in English and the teacher is not native speaker of English. In conclusion, it can be said that the implementation of Content-Based Instruction (CBI) for the teaching of Physics at RSBI class in SMP N 1 Purwodadi is not implemented yet fully based on the theory of CBI.